An Intrinsically Nontrimerizing Peptide Probe for Specifically Targeting Pathological Collagen in Connective Tissues. (20th August 2020) - Cai, Xiangdong; Wei, Wenyu; Bi, Yihui; Liu, Zhao; Bai, Zhongtian; Lei, Junqiang; Xiao, Jianxi
Abstract: The efficient detection of pathological collagen plays an essential role in the diagnosis, prognosis, and treatment of various critical diseases such as arthritis and tumors. Peptide probes with the (Gly‐Pro‐Hyp)n sequences have been recently discovered to recognize pathological collagen; however, their staining efficacy severely suffers from their strong trimerizing tendency. An intrinsically nontrimerizing peptide probe F‐GOP‐10 has been constructed for the first time to specifically target pathological collagen. F‐GOP‐10 consists of the repetitive (Gly‐Hyp‐Pro)n sequences, and displays the single stranded conformation at 0 °C. F‐GOP‐10 has been demonstrated to selectively recognize pathological, but not intact collagen in various mouse connective tissues, and it has been successfully applied to detect pathological collagen in osteoarthritis, liver fibrosis, and various cancer tissues. Compared with the common Masson's trichrome staining method, F‐GOP‐10 displays unique selectivity to only bind to pathological collagen without the interference of intact collagen. Notably, peptide probes with different lengths of the Gly‐Hyp‐Pro triplets all maintain the single stranded conformation, demonstrating their intrinsically non‐trimerizing nature. This pure‐peptide, pure monomer probe allows the accurate concentration determination and the elimination of harmful pretreatment, which has great potential in histopathology staining and other clinical applications. Abstract : An intrinsically nontrimerizing peptide probe is developed for specific recognition of pathological collagen without the interference of intact collagen. It always maintains the single stranded conformation, and has been successfully applied to target pathological collagen in various tissues including osteoarthritis, liver fibrosis, and cancer. This pure‐peptide, pure monomer probe has great potential in histopathology staining and other clinical applications.